Forecasting Methods Proposal and Implementation of Distribution Requirement Planning Method to Overcome Unfulfilled Stock Availability at PT. XYZ - Christine Natalia; Sebastian Gunawan; Yun Chia Liang; Andre Sugioko; Wawan Tripiawan; Marcelinus Fredikson (Fakultas Teknik Universitas Pancasila, 2025)
PT. XYZ is a manufacturing company engaged in the automotive sector by producing various automotive components. Based on the results of observations and interviews at PT. XYZ, it is known that there is a shortage of stock, so that customer or consumer requests are not fulfilled at each existing distribution center (DC). Based on the problems that occur, the research result suggestions for the best forecasting method based on the time series plot of each DC request processing using the Distribution Requirement Planning (DRP) method. In addition, with the DRP method, there is additional stock. The company still has remaining stock so it can still meet customer demand for each DC, and the product distribution process runs more regularly if any defective product should be replaced. Based on research results, the DRP method is able to minimize the risk of unfulfilled demand due to product defects.